Development and Validation of Stability Indicating Assay for Simultaneous Determination of Bupivacaine and Meloxicam in Bulk and Pharmaceutical Formulations by Using Rp-Hplc Method: Pharmaceutical Science-Pharmaceutical Analysis - Stefi Seles, K.; Padmavathi, Dr.Sakinala; Abdul Rahaman, Dr. Shaik; ShabanaAzmi, SK.; ShinyGrace, D.; AmreenSahana, Mohamad (International Journal of Life Science and Pharma Research, 2022)
A simple, rapid, precise, sensitive, and reproducible reverse phase high-performance liquid chromatography (RPHPLC) method has been developed for the quantitative estimation of Bupivacaine and Meloxicam in pharmaceutical dosage form. Aim and objective of our study is to determine the amount of bupivacaine and meloxicam by using RP-HPLC using Waters alliance HPLC system, Quaternary gradient pump of e2695 series equipped with an auto sampler injector with 10μl is injected, and eluted with the mobile phase containing Acetonitrile and Water in the ratio of 60:40 v/v which is pumped at a flow rate of 1 ml/min and detected by UV detector at 225 nm. The peak of Bupivacaine and Meloxicam was eluted at retention times of 2.646 min and 3.136 min, respectively. Chromatographic separation of Bupivacaine and Meloxicam was achieved on Waters Alliancee2695by using Chiralcel ODH 150x4.6mm, 5μcolumn and the mobile phase containing Acetonitrile and water in the ratio of 60:40% v/v. The flow rate was 1.0 ml/min; detection was carried out by absorption at 225 nm using a photodiode array detector at ambient temperature. The number of theoretical plates and tailing factor for Bupivacaine and Meloxicamwere NLT 2000 and kept not more than two respectively. Peak areas, Percentage relative standard deviation of all measurements always less than 2.0. This method was validated according to ICH guidelines. The method was a simple, economical, suitable, precise, accurate & robust method for quantitative analysis of Bupivacaine and Meloxicam study of its stability.